PVDF/PVC blend membrane for CO2/CH4 separation - Sunarti, Abd Rahman; Maity, Bipradeep (2018)
Methane gas is one of the most prevalent gaseous in the air yet it still has its benefits. Global methane emissions from landfill are estimated to be between 30 and 70 million tonnes each year. Most of this landfill methane currently comes from developed countries, where the levels of waste tend to be highest. In this study, a PVDF/PVC membrane was produced in order to separate CH4 gas from the CH4/CO2 mixture. The PVDF/PVC membrane is produced by the combination of Polyvinyl Chloride (PVC), Polyvinylidene Fluoride (PVDF) and Dimethyl formamide (DMF) via dry/wet phase inversion technique. The invention of this PVDF/PVC membrane is expected to improve the characteristics of the polymeric membrane which is the permeability, selectivity and the pore size. PVDF/PVC is introduced with ratio of DMF (solvent): PVDF: PVC 90:10:0, 90:0:10, 90:7:3 and 90:3:7 in order to achieve the desired selectivity and permeability of CH4/CO2 gas separation. From the performance view, the PVDF/PVC membrane with composition 3:7:90 are the most suitable to separate the two gases compared to the rest of the membranes respectively at 1 bar. This high-performance sample are proven by the SEM image of the surface morphology itself. The pore diameter range of 30μm – 35μm.